NYAYA-VAISESIKA ON NUMBER AND ITS PERCEPTION - Biswas, Monalisha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Nyaya and the Vaisesika system are two arthodox (astika) system of Indian Philosophy meaning they admit the Vedas as eternal and infallible that preexist the common era. In their early history, the Nayay and Vaisesika were two Independent system with their own respective metaphysics, epistemology, logic, ethics and solerious. Overtime, the Vaisesika system become so entwined with the Nyaya to the extent that until recently, there was he Independent history of the Vaisesika as a basic system. One reason for addverssing these two systems together is that share many important tents; both systems are committed to common – sense realism and pluralism in their ontology; believe in the creation of the world from material atmos that conjoin to generate. This world by the will of God and in accordance with the accumulated merits and demerits of individual agent. In my article I want to discuss about the Nyaya-vaisesika on number and its perception. The Nyaya-Vaisesika account of number is based on an analysis of our actual - cognitions like ’one’, ’two’, ’three’, etc. They raised the different problems regarding number neither from their interest in mathematics nor from a logistic point of view. We use number words like ’one’, ’two’, ’three’, etc, which in this view designate numbers one, two, three, etc. And numbers for them are as much qualifying features of substances as the qualities like colour, taste, etc. are. They hold a realistic view of number, but such realism should not be confused with Platonism, because numbers in their system are not eternal, timeless, self-subsistent entities known in a priori intuition. A peculiarity of the Nyaya-Vaisesika treatment of number should be noted. The number words like ’one’ or ’two’, do not refer to any single number like one or two. In fact they admit many ones many, twos many threes, etc.